Structure of rrn operons in pathogenic non-cultivable treponemes: sequence but not genomic position of intergenic spacers correlates with classification of Treponema pallidum and Treponema paraluiscuniculi strains - Čejková, Darina (Society for General Microbiology, 2013)
This study examined the sequences of the two rRNA (rrn) operons of pathogenic non-cultivable treponemes, comprising 11 strains of T. pallidum ssp. pallidum (TPA), five strains of T. pallidum ssp. pertenue (TPE), two strains of T. pallidum ssp. endemicum (TEN), a simian Fribourg-Blanc strain and a rabbit T. paraluiscuniculi (TPc) strain. PCR was used to determine the type of 16S–23S ribosomal intergenic spacers in the rrn operons from 30 clinical samples belonging to five different genotypes. When compared with the TPA strains, TPc Cuniculi A strain had a 17 bp deletion, and the TPE, TEN and Fribourg-Blanc isolates had a deletion of 33 bp. Other than these deletions, only 17 heterogeneous sites were found within the entire region (excluding the 16S–23S intergenic spacer region encoding tRNA-Ile or tRNA-Ala). The pattern of nucleotide changes in the rrn operons corresponded to the classification of treponemal strains, whilst two different rrn spacer patterns (Ile/Ala and Ala/Ile) appeared to be distributed randomly across species/subspecies classification, time and geographical source of the treponemal strains. It is suggested that the random distribution of tRNA genes is caused by reciprocal translocation between repetitive sequences mediated by a recBCD-like system.